(untitled) (JURNAL PROTEKSI KESEHATAN, 2021)
soil or known as soil transmitted helminth (STH). Infection caused by these parasites can be eradicated by giving synthetic drugs and herbal medicines. One of the plants that can be used as herbal medicine is ketepeng cina (Cassia alata L.). chinese ketepeng leaves (Cassia alata L.) have one benefit, namely to treat intestinal worms. This study aims to determine the morphological changes of eggs Ascaris lumbricoides after the administration of ethanol extract of chinese ketepeng leaves (Cassia alata L.) with concentration 1%, 2%, 3%, 4%, 5%. The method used in this study is laboratory experiments. The results of this study indicate that the ethanol extract of chinese ketepeng leaves (Cassia alata L.) in concentrated 4% and 5% changes color in the eggs but there is no morphological change in eggs. From this study it can be concluded that the ethanol extract of chinese ketepeng leaves (Cassia alata L.) is not able to damage the morphologi of Ascaris lumbricoides worm eggs.